Natural infection in Pampas fox (Lycalopex gymnocercus) by Lagochilascaris major Leiper, 1910 (Nematoda: Ascarididae) in Buenos Aires, Argentina - Scioscia, Nathalia; Olmos, Leandro Hipólito; Gorosabel, Antonella; Bernad, Lucía; Pedrana, Julieta; Denegri, Guillermo (Springer Netherlands, 2018)
Lagochilascariosis is an emerging parasitic disease limited to the American continent, caused by nematodes of the genus Lagochilascaris. Its life cycle is heteroxenous, involving natural definitive hosts (wild carnivores), accidental hosts (domestic carnivores and humans), and intermediate hosts (rodents). Here we report, for the first time, the occurrence of Lagochilascaris major in female of a Pampas fox (Lycalopex gymnocercus) which was found in the Mar Chiquita basin, Buenos Aires province, Argentina. At necropsy, multiple Lagochilascaris larvae and several adults (1 female and 5 male) were observed inserted in the mucosa of the trachea and a male was also collected in the stomach. The diagnosis was made by observing the different stages with optical microscopy, by scanning electron microscopy of adult males and coproparasitological analysis. Although cases of lagochilascariosis have been reported in wildlife in different countries of the American continent, in Argentina, cases are really rare and were only found in domestic cats.